Struggles and Coping of Primary Caregivers in Raising Children with Autism Spectrum Disorder - William Jo Se Billote (Philippine Association of Institutions for Research, Inc., 2018)
Primary caregivers experience intense confusion before and after they receive an official diagnosis of their child with Autism Spectrum Disorder (ASD). Although the quest to help their child may alleviate some negative feelings, the stress increases when they realize that there is no cure for ASD. This study employed a descriptive comparative design which aimed to compare and contrast the struggles of 93 primary caregivers and their coping strategies in terms of gender and their relation to the child with ASD in Baguio City, Benguet and Dagupan City, Pangasinan. Inventory questionnaires were utilized to gather data. Using Mean Analysis and ANOVA, the more prevalent struggles experienced by the primary caregivers are Financial and Emotional. Males experienced Financial struggle the more while females experienced Emotional. Blood-related primary caregivers struggle more with Financial and Emotional while non-blood related primary caregivers struggle with Health. With the struggles they encounter, the more prevalent coping strategies utilized by primary caregivers are Problem Solving and Social Support. Males utilized Problem Solving the more while females utilized Social Support and Emotional Expression. Blood-related primary caregivers utilized Problem Solving more while nonblood-related primary caregivers utilized Social Support. Despite the various struggles primary caregivers encounter, they find ways to cope with them.